Development of a Self-Directed Learning E-Module to Enhance Students' Critical Thinking in Islamic Cultural History - Kamalasari, Dikriati; Hadeli, Hadeli; Misra, Misra; Nurdin, Syafruddin; Sari, Milya (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This study was motivated by the low level of students' critical thinking skills in Islamic Cultural History (ICH) learning at Madrasah Tsanawiyah, which is largely dominated by conventional, teacher-centered instructional practices. The study is theoretically grounded in constructivist learning theory and the concept of Self-Directed Learning (SDL), emphasizing learner autonomy, reflection, and responsibility. Within the context of Islamic education, critical thinking is also seen as an embodiment of ulul albab values, integrating reasoning, reflection, and moral awareness. The purpose of this study was to develop a Self-Directed Learning-based E-Module for Islamic Cultural History that is valid, practical, and effective in enhancing students' critical thinking skills, while contributing to inclusive and contextual learning. This research employed a Research and Development approach using the 4D model (Define, Design, Development, and Disseminate). The study was conducted with eighth-grade students at MTsN 2 Padang. Data were collected through observations, interviews, questionnaires, and critical thinking tests. The dissemination stage was implemented on a limited scale through digital distribution of the E-Module. The findings indicate that the developed E-Module demonstrates very high validity (94.11%), high practicality according to teachers (91%) and students (95.82%), and is effective in improving students' critical thinking skills, as shown by an average N-Gain score of 0.727 (high category). The novelty of this study lies in integrating Self-Directed Learning into Islamic Cultural History E-Modules to foster critical thinking and prepare students for constructive participation in Indonesia's multicultural society.